Epibulbar Plasmacytoma Masquerading as Subconjunctival Hemorrhage in a Patient With Multiple Myeloma. Issue 2 (16th November 2016) - Bradley, Amanda; Estes, Amy; Ulrich, Lane; Thomas, Dilip; Gay, David
Abstract : Purpose: We report a 75-year-old woman with a history of multiple myeloma immunoglobulin D (IgD) variant, who presented with an epibulbar plasmacytoma masquerading as a subconjunctival hemorrhage. Methods: Magnetic resonance imaging of the brain and orbits with and without contrast was obtained and surgical biopsy of the subconjunctival lesion was performed; histopathology confirmed the diagnosis of plasmacytoma. Results: Subconjunctival biopsy revealed a plasma cell neoplasm infiltrate in the episcleral layer. The subconjunctival biopsy stained positive for CD138 and lambda-immunohistochemistry in the majority of plasma cells. Histologic findings were consistent with involvement by known IgD plasma cell myeloma where previous bone marrow biopsy demonstrated myeloma cells which stained monoclonally for IgD-lambda light chains. Conclusions: Although plasma cell neoplasms seldom present with ocular manifestations, it is crucial to recognize that these tumors may be associated with multiple myeloma. In patients with known multiple myeloma who present with subconjunctival hemorrhage, close follow-up is highly recommended, as this may be the initial presentation of an ocular plasmacytoma. Although a plasmacytoma is a rare subconjunctival lesion, it should not be immediately excluded from the differential diagnosis of such lesions.